E-(ternal) grieving: The digitalization and redefining of death and loss on social media - Izmy Khumairoh (SIMULACRA: JURNAL SOSIOLOGI, 2023)
The practice of grieving from a socio-cultural perspective is never an impersonal matter. The attachment to different organized values and habits prevents the individual from determining the attitudes and emotions that must be shown when grieving. This fact raises the question of the place of traditional mourning practices in society amidst the invasion of new technologies, i.e. social media. The study uses qualitative methods to analyze some Instagram content related to mourning the loss of several public figures in Indonesia. In the case studies examined, the contribution of big technology gives us autonomy, but it is only a phantasmagorical one. Ultimately, our identities will continue to control what we do in cyberspace and in the natural world. Social media is only an alternative space for the manifestation of correlated socio-cultural values, including the implementation of norms in mourning. Nevertheless, the freshness offered in the practice of mourning on social media is that people can now immerse themselves in a longer liminal period and preserve the communication and social status of the deceased with the available function of perpetual mourning. The results of the study should stimulate further research on how technology can shape society in the digital age.